On the legitimacy and effectivity of the world bank and its pandemic emergency financing facility ('PEF') at the time of the covid-19 outbreak - Seatzu, Francesco (International Organizations Law Review, 2021)
Pandemic financing has in the current climate of disruption and turmoil of an ongoing global pandemic become the most highly debated and controversial issue within the field of international public health law and policy. From the perspective of international public health law and policy, a precondition for success is that financial resources and funds are employed in an effective manner. Whether the International Bank for Reconstruction and Development (‘World Bank’ or ‘WB’) and the Pandemic Emergency Financing Facility (‘PEF’) – a financing mechanism housed at the WB – may be perceived as effective public health players shall be established by referring to their mandates, their inherent capacity for enhancing accepted global legal standards and rules on public health and their funding methods and practices. After the affirmation and consolidation of its role in the public health sector in the early 1990s, the WB has rapidly accredited itself as the most active intergovernmental institution dealing with pandemic and epidemic financing. Its direct involvement in public health trust funds, such as the Avian Flu Trust Fund Facility and the Health Emergency Preparedness and Response Multi-Donor Fund (the HEPRF), and its lending practices and internal policies and procedures were of crucial significance in this respect. Considering that acceptance of international institutions, including international financial institutions, has always been conditioned by their acknowledgment as legally legitimate, legitimacy is regarded as closely connected to effectiveness. The criteria for establishing legitimacy in relation to international financial institutions are increasingly, amongst others, the respect and promotion of rule of law standards in the recipient states. From this perspective, the WB’s functional and management structures, but not the PEF’s structures and management, have made noteworthy progress, and notwithstanding some deficiencies and peculiarities they present several elements of legitimate decision-making.